Strategi Pembelajaran PAK Anak di Era Digital dan Pengaruhnya Terhadap Pertumbuhan Rohani Anak Dalam Jemaat RPCC Cambridge Medan - Imeldawati, Tiur; Marbun, Nurmiati; Nainggolan, Eka Nurlela (STT Injili Indonesia Medan, 2023)
The Christian education learning strategy can be interpreted as an effort made by a person or organization to arrive at a goal, in this case to achieve the goals of Christian Religious Education. Some of the things behind this research include the author observing that the implementation of Christian education in the RPCC congregation is still running sober and has not been able to keep up with the times, besides that it was found that the serving teachers also seemed unprepared in abilities or skills related to mastery of strategies that answered needs in the midst of child services. The next thing found from observations is children who have not experienced spiritual growth, this can be seen from their lack of enthusiasm in worship and in everyday life because children do not yet reflect spirituality which shows progress according to their age development. The purpose of this study is first, to explain the importance of learning strategies for Children's Christian Religious Education in the digital era carried out at RPCC Cambridge Medan. Second, describes the teacher's lack of optimality in carrying out learning strategies in the digital era. Third, explaining the spiritual growth of children at RPCC Cambridge Medan. Fourth, prove how big the influence of children's PAK learning strategies in the digital era is on the spiritual growth of children at RPCC Cambridge Medan. With the quantitative method chosen by the researcher, direct data were obtained from respondents in the research field and it is hoped that it will become a driving force for improving child services at RPCC Medan.Â Keywords: digital era, child services, strategy